Knee joint forces in the "Serra da Estrela" territory: the Trails4Health project - Mário Jorge Costa; José Bragada; Catarina Santos; Natalina Casanova; Jorge Casanova; Raúl Bartolomeu (Desafio Singular, 2019)
The aim of this study was to characterize knee joint forces in different trails from the Serra da Estrela with distinct characteristics. Twenty-nine subjects (20 males and 9 females), mean of 28.04±10.79 years, 1.73±0.09 m of height and 69.59±11.00 kg  of body mass volunteered for this study. In separate days, all subjects underwent three hikes (trail 1: circular, 10970m; trail 2: linear, 9053m; trail 3: circular, 7536m). A GPS device (Fenix 5, Garmin, USA) was used to ensure a consistent 5 km·h-1 pace and tracking the slopes. The knee joint forces, namely the maximum patellofemoral compressive force (MaxPcF), the maximum tibiofemoral shear force (MaxTsF) expressed as times the body weight (xBW) and the load equivalent (LE) were estimated. The MaxPcF was 2.1, 1.8 and 2.1, and the MaxTsF was 0.83, 0.80 and 0.83 for trails 1, 2 and 3, respectively. The MaxPcF for trail 1 is equivalent to a flat 17386 m walk and MaxTsF is equivalent to a 10980 m walk. The MaxPcF for trail 2 is equivalent to a flat 12605 m walk and MaxTsF is equivalent to a 8320 m walk. The MaxPcF for trail 3 is equivalent to a flat 12357 m walk and MaxTsF is equivalent to a 7532 m walk. According to the LE, trail 1 can be classified as "moderate", and trails number 2 and 3 are classified as "pleasant". Main data suggests that trail number 2 elicited less knee compression and shear forces. In contrast, trails number 1 and 3 are less appropriate for those who suffered from previous knee pain.